A second C-reactive protein (CRP) test to detect inflammatory burst in patients with acute bacterial infections presenting with a first relatively low CRP. Issue 42 (16th October 2020) - Goldberg, Ilan; Shalmon, Dana; Shteinvil, Ronen; Berliner, Shlomo; Paran, Yael; Zeltser, David; Shapira, Itzhak; Shenhar-Tsarfaty, Shani; Meilik, Ahuva; Wasserman, Asaf; Goldiner, Ilana; Ziv-Baran, Tomer; et al.
Abstract : Abstract: A first C-reactive protein (CRP) test, as often performed by clinicians during the presentation of patients with an acute bacterial infection, might be misleading. The aim of our study was to explore the dynamic between a second CRP test taken within 12 hours from admission CRP test in a cohort of patients diagnosed with acute bacterial infection in comparison to CRP in a control group of apparently healthy individuals. This was a historical cohort study comprised of all patients admitted to the Sourasky Tel-Aviv Medical Center, Israel, between July 2007 and March 2016. The study cohort included adult patients who were diagnosed as having an infection, assumed to be of bacterial etiology (cellulitis and erysipelas, pneumonia, cholecystitis, pyelonephritis, or septicemia), who had a CRP test during the first 6 hours of hospital admission (baseline CRP), and a successive CRP test up to 12 hours from the first one (recurrent CRP). The control group was of healthy subjects who attended our medical center for a routine annual check-up. The study included 950 patients. Baseline CRP ranged from 0.04 to 454 mg/L. The median CRP velocity was 0.53 mg/L/h. Patients were grouped by baseline CRP into 4 groups (CRP < 10, 10–74.9, 75–199.9, ≥200). There was an increase in median CRP velocity between the first (0.48 mg/L/h) and the second (0.93 mg/L/h) groups, which then was decreased in the next 2 groups (0.46 and −2.58 mg/L/h, respectively). In 45 of 103 (44%) patients of the group of baseline CRP concentration less than 10 mg/dL with bacterial diagnosis, there was a complete overlap with CRP values of apparently healthy individuals during their routine annual checkup. A first single low CRP result cannot exclude the presence of a significant bacterial infection. Patients with acute bacterial infection might present with a relatively low CRP value that at times correspond to normal limit CRP concentrations. A second test, obtained within 12 hours of admission, might serve as an important tool to identify patient with an evolving inflammatory burst commonly seen during acute bacterial infection.